THE ROLE OF E-SERVICE QUALITY, CUSTOMER SATISFACTION, AND EXPERIENCE IN REPURCHASE INTENTION ON TRAVELOKA USERS IN BANDUNG - Kurniawan, Ryan; Rachmawati, Mariana; Suganda, Uce Karna (PT. Altin Riset Publishing, 2025)
This research is intended to find out how the role of consumer satisfaction mediates the effect of service quality and customer experience on repurchase intention. To identify the relationship between e-service quality and repurchase intention through customer satisfaction as a mediation, the relationship between customer experience and repurchase intention through customer satisfaction as a mediation, the relationship between customer satisfaction and repurchase intention, the relationship between customer experience and customer satisfaction, and the relationship between e-services. service quality to customer satisfaction for Traveloka customers. The data collection method used a questionnaire research instrument in the survey method. The object of this research is 110 respondents who are Traveloka customers who are domiciled in Bandung and aged 17 years and over. The research method applied is a quantitative method using the SPSS data analysis program. The research results show that e-service quality and customer experience have a positive and significant effect on customer satisfaction. E-service quality, customer experience, and customer satisfaction have a positive and significant effect on repurchase intention.